Spherites in the midgut epithelial cells of the sugarcane borer parasitized by Cotesia flavipes - Pinheiro, Daniela De Oliveira [UNESP]; Conte, Hélio; Gregório, Elisa Aparecida [UNESP] (My University, 2008)
Diatraea saccharalis, the main pest of sugarcane, has been controlled by Cotesia flavipes. Very little is known about the effect of parasitism on the host organs, including the midgut. The Lepidoptera midgut epithelium is composed of columnar, goblet, regenerative, and endocrine cells. Spherites have been described in columnar and regenerative cells of several Lepidoptera species, and presented a lot of functional meaning. We identified spherites in the midgut epithelial cells of non-parasitized D. saccharalis larvae analyzed the effect of parasitism on spherite morphology and distribution along the length of the midgut. Midgut fragments of both non-parasitized and parasitized larvae were processed for transmission electron microscopy. All the midgut epithelial cells showed spherites, but they were not preferentially located in a particular part of the cells. Parasitized larvae had more spherites, mainly in the columnar cells, than non-parasitized larvae. This observation was associated with an ionic imbalance within the insect host. Spherites were more abundant in the anterior midgut region than in other regions, which suggests that this region is involved in ion transport by intracellular and/or paracellular route. The morphological variability of spherites in the cells of parasitized larvae was related to the developmental stages of these structures.
Keywords: Epithelial cell; Lepidoptera; Parasitism; Spherite; Ultrastructure